APLIKASI TIKTOK SEBAGAI MEDIA PEMBELAJARAN BAHASA ARAB DI ERA DIGITAL - Hamzah, fatahillah (AL MUALLAQAT, 2023)
The TikTok application has become a phenomenon in the current digital era, with millions of active users every day. In the context of Arabic language learning, this application can serve as an innovative and engaging resource to enhance the learning experience. The aim of this journal is to explore the potential of using the TikTok app as a medium for Arabic language learning, identify the associated benefits and challenges, and explore ways to optimize its use in an educational context.